Variacion estacional en el Lago de Rio Cuarto, provincia de Alajuela, Costa Rica. II Distribución estacional del zooplancton - Ramírez, Elizabeth (1990)
Several limnological studies were carried out between February 1984 and March 1985 in Río Cuarto Lake. Composition of the zooplanktonic community seasonal changes and vertical distribution of the most abundant zooplankton species were determined, and correlated with the results of chemicals, physical and biological data. The rotifers were the most important group in the zooplanktonic community. The rotifers identified were Keratella americana, Polyarthra vulgaris, Pompholix complanata, Hexarthra intermedia, Euchlanis diladata and Lecane sp. In addition the cladocerans Diaphanosoma spinulossum and Bosmina longirostris and a copepod Microcyclops varicans were found.The greatest zooplanktonic diversity was found during the rain seasons, which were characterized by higher oxygen concentrations in the water column.On the other hand the dry season favored population increments during which period the density of the zooplanktonic community was the highest. The most important food sources for zooplankton were phytoplankton, bacteria and detritus.